The Effect of Graded Levels of Dietary Methionine on the Haematology and Serum Biochemistry of Broilers - Adeyemo, G.O.; Ologhobo, A.D.; Adebiyi, O.A. (International Journal of Poultry Science, 2010)
Graded levels of dietary methionine on the haematology and serum biochemistry were investigated in broilers. One hundred and fifty broiler chicks (Arbor acre breed) were use, the chicks were divided into 5 treatments consisting of 6 replicates of five chicks each. The chicks were kept in floor pens. The study lasted for 56 days at the teaching and research farm of the university of Ibadan Nigeria. No significant differences (p>0.05) were observed in the PCV, RBC and WBC values of broilers fed the different levels of methionine inclusion, at the finisher phase, but at starter phase significant differences (p<0.05) were observed, with the WBC values increasing as the inclusion rate of methionine increased. Total protein value of 4.80g/100ml and 4.48 g/100 ml were obtained for treatments 4 and 5 respectively which were not significantly (p>0.05) from each other. There were wide variations in the glucose concentration of the birds, the highest glucose concentration was observed with birds on diet 2 (220.90) while the least was observed for birds fed the control diet though significant differences (p<0.05) were observed it did not follow a particular order.